Diversified multitier cropping systems for west coast of India - Kumar, Parveen; Arunachalam, V; Paramesha, V; Maneesha, S R (Indian Farming, 2021)
The multitier system can become a complementary enterprise, saves land, labor, and resources, enhances income, biodiversity conservation, and soil fertility under coastal region of the country. The selection of component crops for the multitier cropping system should be based on the location, soil, and climate suitability, market demand, family requirement, available farm resources, etc. Besides the yield and income, the multitier system also addresses partially the nutritional security and the issue of unemployment and has the potential to produce around the year income.